Web Based Petanque Sports Match Statistics - Aidilla Pratiwi Siregar; Ibrahim Sembiring; Albadi Sinulingga (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2023)
This research aims to (1) Produce a product on web based Petanque sport match statistics , (2) Find out the use of Petanque sport match statistics. This research uses the Research and Development Method ( R & D) refers to the development model from Borg and Gall through 8 stages , namely: (1 ) Potential and problems, (2) Information collection, (3) Product design, (4) Design validation, (5) Design revision, ( 6) Small scale trial, (7) Revision of small scale trial, (8) Large scale trial, (9) Final product. The subjects of this research during small group trials during routine training were 7 athletes and 4 coaches. During the trials, the large group consisted of 10 athletes and 8 coaches during the Sumut-Aceh PON XXI PELATDA Selection. The results of this research are (1) A web based statistical product for Petanque sports competitions to find out to what extent the athlete's abilities are during training. (2) The level of suitability of this product is determined through expert validation assessment. (3) Development and development of match statistics. The web based petanque match statistics application meets the criteria or is very feasible to use. It is proven that the development of web based Petanque match statistics is feasible to use.